Socialinių santykių atspindžiai Rytų Lietuvos pilkapių degintinių kapų medžiagoje - Kurila, Laurynas (Archaeologia Lituana, 2002)
Excavation of burial mounds of East Lithuania began in the middle of the 19th century. Over one third of burial mound cemeteries have been excavated. Multiple articles on burial traditions, material culture and ethnic structure of the population of East Lithuania are based on these data.However, in spite of the considerable number of excavated burial mounds, matters of demography and social structure are still obscure. There are several obstacles to such sorts of investigations.No burial mound cemetery has been excavated completely. Therefore, data can hardly be used for conclusions that require statistical analysis. The custom of cremation of the dead had predominated in the eastern part of Lithuania for approximately seven centuries. Cremated bones have been analyzed anthropologically only on a very small scale. For that reason the possibility of correlating the burial traditions or the complex of grave goods and the sex or age of the buried person is limited.This article is based on the data of 66 graves analyzed anthropologically by Assoc. Prof. R. Jankauskas. The purpose of the article is a survey of the connections between the archaeological and anthropological material of the burial mounds of East Lithuania.The analysis of cremated bones is burdened by the fragmentary nature and deformation of the material. Precise determination of the individual’s age is seldom possible. The sex of the cremated individuals might be determined correctly in about 80 per cent of the cases (by comparison of the anthropological data with the available grave goods).No noticeable relation was observed either between sex and the size of the burial mound or between sex and the location of the grave in the mound. Thus, the burial rite was not used as a means to emphasize the sex of the individual. However, the burial of different age groups definitely varied. The number of graves of newborns and infants in the burial mounds of East Lithuania is far smaller than that in other cemeteries of the same period. Infants under about five in most cases appear not to have been buried like adults. The infant graves might have been located in separate groups of mounds or outside the cemeteries. Children up to the age of 12–15 were often buried in one mound or even in one grave with the adults. Only in some cases was a new mound built when burying a child. Most commonly children’s graves were placed in a mound previously built for an older person. Those who reached adolescence were buried in the same way as the adults, more often in a newly built mound. The difference between the burial of individuals of 20–40 years of age and those over 40 is imperceptible.The comparison between age and the complex of grave goods also displays some tendencies. The majority of individuals buried without any artifacts were of the older age classes (probably an average age of 35–40), while all the graves of children and juveniles contained metal goods. The inventory of girls’ or teenager females’ and adult women’s graves did not differ much in their composition or in abundance. Tangible differences are visible in masculine graves, however. More abundant goods were placed into the graves of youth and young adults. Elder men were buried with a smaller number of weapons and other goods. This phenomenon most likely reflects the predominant status of young and physically strong men in the Iron Age society of East Lithuania. Some graves of adults buried together with children were also comparatively wealthy. In most cases the goods in these graves seem to be dedicated primarily to the children.The available scanty anthropological data of the burial mounds of East Lithuania still are not sufficient for demographic research. For the same reason, the connection between sex and age of the buried individuals and certain elements of burial mounds that have regional and chronological differences was deliberately omitted. In the future, the analysis of the material of one well-excavated burial mound cemetery is likely to render more significant results.